E-module practicum of plant tissue culture with augmented reality to enhance lateral thinking and digital literacy - Manisa, Tesa; Nawawi, Nawawi (STKIP Persada Khatulistiwa Sintang, 2025)
Plant tissue culture is a course requiring both theoretical understanding and practical skills in observation and analysis. Observations at the plant tissue culture laboratory of PGRI Pontianak University indicated that many students struggled to analyze culture stages, calculate appropriate media composition, and faced equipment limitations. This study aimed to determine the validity, practicality, and effectiveness of an augmented reality-assisted e-practicum module. The research employed an R&D approach with the ADDIE model. Data were collected through validation sheets, practical questionnaires, and lateral thinking skill tests for prospective teacher students. Data analysis involved calculating validation scores, questionnaire results, and N-Gain scores. The findings showed that the AR-assisted e-practicum module was valid in material aspects with an average score of 80 and very valid in media aspects with a score of 82. Student responses indicated the module was very practical, with an average score of 82%. The effectiveness test yielded an N-Gain score of 0.71, categorized as high. These results demonstrate that the AR-assisted e-practicum module can enhance students’ lateral thinking skills and digital literacy, suggesting its potential as a valuable teaching tool for future use.